2017
DOI: 10.1108/ijoem-04-2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging domestic and foreign learning to develop marketing capabilities

Abstract: This study explores the role of different learning sources in the process of capability building of Chinese firms (CFs) approaching international markets. Design/methodology/approach The paper is based on the case study of the company "Goodbaby". The primary data sources are two semi-structured interviews with one of the firm's managers, which have been triangulated with point of sales (POSs) visits, interviews with industry experts, and secondary data such as corporate records, patent and trademark data, indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…Our sample diverges from learning effects observed in other contexts by indicating that foreign and domestic acquisition experiences tend to have opposite effects on Chinese CBA capabilities. For example, Checchinato et al (2017) found that Chinese companies can leverage learning from both domestic and foreign market experience to support marketing capabilities in domestic and international markets. However, experiential learning is more ambiguous in complex M&As than it is in normal commercial activities.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Our sample diverges from learning effects observed in other contexts by indicating that foreign and domestic acquisition experiences tend to have opposite effects on Chinese CBA capabilities. For example, Checchinato et al (2017) found that Chinese companies can leverage learning from both domestic and foreign market experience to support marketing capabilities in domestic and international markets. However, experiential learning is more ambiguous in complex M&As than it is in normal commercial activities.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Considering the fact that authors from the different countries cooperate with each other, in order to obtain unambiguous results, we applied the lead author's affiliation as a determinant for the articles being discussed. The majority of the studies included in our analysis have been conducted on the USA (Engel and del-Palacio 2009, DeFillippi 2015, Bagchi-Sen and Scully 2004, Sahaym et al 2012, Cunningham and Link 2015, Pett and Wolff 2009, Hegde and Shapira 2007, Snow et al 2011, Acworth 2008, Levina and Vaast 2008, Rodriguez et al 2013, Vasudeva 2009, Wu et al 2016, followed by Italy (Archibugi and Coco 2001, Archibugi and Coco 2005, Cerrato and Piva 2015, Checchinato et al 2017, Colombo et al 2016, Dell' era and Verganti 2009, Di Matteo et al 2015, Fabrizi et al 2016, Geisler and Turchetti 2015, Greco et al 2016, Johnson and Filippini 2010. Paradoxically, a lot of articles on a given subject were written by the authors from Italy, although most of them do not describe the situation in this country, but refer to others, such as the USA, Japan, China and the whole of Europe.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Government ownership, on the other hand, has a direct impact on internationalization. Thus, it is important to consider that strategic choices are not only influenced by firm-specific resources, but also can be the response to the institutional framework in which the firm is embedded (Checchinato et al, 2017;Kittilaksanawong, 2017;Wang et al, 2012). At the same time, government policies may not be able to exert a direct effect on firm behaviors, but only indirectly through the influence on strategic intents or motives.…”
Section: Theoretical Implicationsmentioning
confidence: 99%